Pelatihan Pembuatan Pupuk Organik dengan Penggunaan Biostater pada Kelompok Tani Rukun Makaryo Desa Pereng Mojogedang Karanganyar - Putri Permatasari; Joko Winarno; Sapja Anantanyu; Suwarto Suwarto; Agung Wibowo (Universitas Muhammadiyah Semarang, 2021)
Local knowledge is the various works and initiatives of a certain community which are believed to be useful for fulfilling part of their daily needs. This local knowledge can take the form of a set of knowledge and skills in creating something that is believed to be very useful. The source or origin of local knowledge and skills is generally acquired from generation to generation or the result of paying attention to and practicing it yourself over and over again the result of the experiences of others arround it. The use of this local knowledge has been empirically believed and proven by local community from time to time. One of the works of the Rukun Makaryo Farmer Group, Pereng Mojogedang village, is the ude of cattle rumen and its contents as a biodecompuser in the process of fermentation of solid wate from castle to fermented solid organik fertilizer. The rationale is very simple, namely in the rumen of cows there are bacteria that can destroy various forages that are eaten by cows. Therefore, if the bacteria can be cultivated outside the cow’s stomach, it can be used to overcome the abundant solid wate of cattle in rural areas to become solid organik fertilizer needed by farmers.